Fiber intake and physical excercise contributed to blood glucose level in outpatients with type 2 diabetes mellitus - Rijanti Abdurrachim; Rizqi Dwi Annisa (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2017)
ABSTRACTBackground: Education, diet plan, pharmacologically and physical exercise are factors that can change the status of blood glucose levels. A low level of knowledge can affect the wrong dietary habit. DM patients are suggested to consume fiber as much as 25 g/ day.  Objectives: The article aimed to analyze the level of knowledge, fibers intake and physical exercise of type 2 DM patients’ blood glucose levels at Internal Disease Polyclinic of RSUD Ulin Banjarmasin.Methods: This study used observational analytics method with cross- sectional design. The population of this study were type 2 DM patients and had been checked for the fasting blood glucose levels at Internal Disease Polyclinic of RSUD Ulin Banjarmasin in April 2017. There were 47 samples that were taken by using purposive sampling. To collect food intake data, questionnaire food recall. The data analysis used Spearman’s correlation test rank and regesi logistic (mulivariate ) with 95% of confidence level.Results: The result showed that 66% of blood glucose levels were uncontrolled, 40.4% of knowledge level were average, 68.1% of fibers intake was less, and 57.4% of physical exercises were less. Level of knowledge, intake of fiber, physical exercise contributed to blood glucose levels. The level of glucose levels closeness to the knowledge level was very strong with r = -0.7783 and that of to fiber intake and physical exercise were moderate level with r = -0.471 and r = -0.381.Conclusions: Fiber intake and physical exercise are significantly associated with blood glucose in patients with type 2 diabetes outpatient. KEYWORDS : DM type 2, the level of knowledge, fiber, physical exercise, blood glucose.